Soil mechanics and foundations - Sewick, Marian (SCITUS Academic LLC, 2016)
The study of rock and soil as construction and load bearing material goes hand in hand with the background knowledge of the geological process of formation and the environmental effects on such formations. Soil is the combination of rock, mineral fragments, organic matter, water and air. It is mostly made up of grains of rock and humus. The type of soil depends on the mix of humus and on the size of the grains of the rock. Soils are the oldest and the most used building materials. Soil mechanics and foundations engineering covers that how to solve certain fundamental problems related to consolidation, shear strength, and design of shallow and deep foundations; and familiarizes students with relevant terms and soil tests so that they can work effectively with geotechnical engineering specialists. Soil Mechanics and Foundations emphasizes on the basic concepts and principles of soil mechanics and foundations in the context of basic mechanics, physics, and mathematics. Soil Mechanics and Foundation is reference tool for engineers, scientific researchers, and construction and design specialists with the up-to-date achievements in soil mechanics theory, experimental investigations, geotechnical and foundation engineering problems and innovative solutions, design and construction practice in regions with steady and exciting soil conditions.